Decisions regarding antibiotic prescribing for acute sinusitis in Norwegian general practice. A qualitative focus group study - Jorunn Thaulow; Torunn Bjerve Eide; Sigurd Høye; Holgeir Skjeie (Scandinavian Journal of Primary Health Care)
Background Acute sinusitis is a frequent reason for primary care visits. Most patients recover within two weeks without antibiotic treatment. Despite this, about 50% of patients with acute sinusitis in Norwegian general practice are still prescribed antibiotics. We do not know the reason behind this discrepancy.Aim To explore the clinical decision-making process and reasons for treatment with antibiotics for acute sinusitis among Norwegian general practitioners (GPs).Methods Five focus group interviews were conducted (N = 25) in different parts of Norway, including GPs of various age, gender, and experience. The interviews were analysed using Systematic Text Condensation.Results The results showed a very diverse management of acute sinusitis among GPs, with decisions regarding antibiotics not always aligning with guideline recommendations. Many of the GPs did not agree with the Norwegian guidelines for antibiotics and chose something other than phenoxymethylpenicillin as their first choice. Clinical predictors emphasized in decision-making were pain complaints and patient exhaustion. Pragmatic factors such as weekday, travel plans, or a full waiting room could also influence the decision.Conclusion GPs found it difficult to identify when patients would benefit from antibiotic treatment for acute sinusitis, and different strategies were used to make prescribing decisions. For several GPs the degree of pain was one of the decisive reasons for antibiotic prescribing, however the guidelines for antibiotics do not give sufficient advice regarding pain treatment. These results suggest a need for revaluation of guideline contents and the way they are communicated to GPs.